A Rare Cause of Acute Renal Failure: Retroperitoneal Fibrosis - Yılmaz, Omer; Kizilkan, Yunus Emre; Temel, Muhammed Cihan; Ediz, Caner; Ozcelik, Fatih (Journal of Clinical Case Reports and Images, 2019)
Idiopathic retroperitoneal fibrosis also known as Ormonds disease is a rare disorder characterized by the development of fibrotic tissue in the retroperitoneum. The fibrotic tissue may compress ureters, leading to obstructive nephrouropathy and renal failure. A 58-year-old man with fatigue, loss of appetite and unable to urinate was admitted to our clinic. Because of the serum creatinine value of 5.3 mg/dl, urinary ultrasonography was performed and bilateral grade 3 hydronephrosis with moderate level urine in bladder was detected. Hydronephrosis did not regress by transurethral foley catheter and suspicious appearance in the retroperitoneal area was found in abdominal magnetic resonance imaging. Tru-cut biopsy result of the current lesion was finally reported as a connective tissue. Bilateral double j catheter insertion was performed and started to immunosuppression therapy with corticosteroid. Two months later, double j catheters were removed and hydronephrosis was not detected in follow-up. In this case report, we tried to explain that, retroperitoneal fibrosis should be considered in the differential diagnosis of postrenal acute renal failure, even in patients without a classic symptom such as pain. In addition, early surgical intervention should be avoided in such patients.
Keywords: Retroperitoneal Fibrosis; Acute Kidney Injury; Hydronefrosis